EKSTRAK ETANOL LIMBAH KULIT BUAH KAKAO (THEOBROMA CACAO L.) SEBAGAI BAHAN BAKU BERPOTENSI OBAT - Herman Herman; Indica Septriyanti; T Rahmat Ramadhani; Putri Ade Rahma Yulis; Arief Yandra Putra (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
Cocoa fruit is one of the fruits with local wisdom that can benefit Indonesia. But its used still limited to the fruit, while the peel of the cocoa fruit is only discarded so that it becomes a waste that will have an impact on the surrounding environment. We can minimize the amount of waste from the peel of the cocoa fruit is to make something useful that is a potential drug raw material. In this study a qualitative test was conducted to determine the secondary metabolite content of the cocoa plant. Flavonoid test results have positive results that indicate a change in color. The results of phenolic and tannin testing have positive results that indicate the formation of bluish black or green. Saponin test results have positive results that indicate the formation of foam. Triterpenoid test results did not show positive results. Based on the results of the study, cocoa peel waste has the potential to be used as an alternative to potentially medicinal raw materials.